From buildings and loans to bail-outs: A history of the American savings and loan industry, 1831-1995 - Mason, David Lawrence (Cambridge University, 2013)
First appearing in the 1830s, savings and loans, then known as building and loans, encourage their working-class members to adhere to the principles of thrift and mutual cooperation as a way to achieve the "American Dream" of home ownership. This book traces the development of this industry, from its origins as a "movement" of a loosely affiliated collection of institutions into a major element of America's